Optimalisasi Potensi Pelajar SMAN 05 Kepahiang untuk Menghadapi Tantangan Global - Jon Hardi (JPT : Jurnal Pendidikan Tematik, 2025)
This study aims to optimize the potential of students at SMAN 05 Kepahiang in facing increasingly complex global challenges. Along with the development of the era, students are required to have relevant skills and knowledge in order to compete in the international world. Therefore, this study identifies various factors that influence the development of student potential, such as curriculum, facilities, and teaching methods applied in schools. Through a qualitative approach with observation and interview methods, the results of this study reveal the importance of strengthening 21st century skills, such as critical thinking skills, communication, and collaboration. In addition, this study also highlights the need for support from parents, the community, and the government in creating a conducive learning environment. Based on these findings, it is recommended that schools update their curriculum to be more adaptive to technological developments and introduce relevant life skills training. With these efforts, it is hoped that students at SMAN 05 Kepahiang can be better prepared to face global challenges in the future.